Impacts of pastoralists on woodlands in south Turkana, Kenya: Livestock-mediated tree recruitment - Reid, Robin S.; Ellis, J.E. (1995)
Since the turn of the century, African pastoralists have been held responsible for overuse of woody plants and for the degradation and desertification of many arid and semiarid lands. We analyzed the impacts of pastoral nomads and their livestock on the recruitment (establishment to first reproduction) of Acacia tortilis, a dominant tree in the dry woodlands of South Turkana, Kenya, where Acacia seedpods make up an important part of livestock diets. Seed density averaged over 85 times higher in bush-fenced livestock corrals than in the surrounding environment. The survival and growth of 14 cohorts of trees ranging in age from 1 to 39 yr were investigated comparing tree stands originating inside livestock corrals with those originating outside. Corral soils contained nine times more C, three times more N, and six times more P than adjacent noncorral soils immediately following corral abandonment. Corral soils also retained more moisture than noncorral soils after rainfall. These soil conditions accelerated seedling emergence in corrals, and enhanced survival and growth of 1st-yr seedlings. Survival of older trees in corral stands was not significantly different from those established outside corrals during this study. However, comparison of tree densities over time suggests that corral stands thin more rapidly than noncorral stands, probably because of crowding. The early survival and growth advantages of the corral environment appear to stabilize the reproductive patterns of A. tortilis in this arid ecosystem, where successful recruitment in noncorral sites may be restricted to the few years with high rainfall. Contrary to the conventional wisdom, pastoralists may be improving rangelands in South Turkana by enhancing recruitment reliability in this important tree species.